Recurrent ipsilateral ectopic pregnancy after partial salpingectomy: case-report - Ratsiatosika, Tanjona Andriamanetsiarivo; Randriamahavonjy, Romuald; Abasse, Baco Abdallah; Fnat, Mahefarisoa; Housni, Ibrahim; Andrianampanalinarivo, Rakotovao Hery (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Ectopic pregnancy is a life-threatening condition occurring in 1-2% of all pregnancies. The most common site of implantation for an ectopic pregnancy is the fallopian tube. Authors report a case of recurrent ipsilateral ectopic pregnancy following right partial salpingectomy of a 29-Year-Old woman that led to tubal rupture. The pregnancy was conceived spontaneously. Diagnostic of ruptured ectopic pregnancy was done after clinical and ultrasonography examination. The presence of a massive hemoperitoneum with a positive pregnancy urinary test that lead us to the diagnosis of ectopic pregnancy. She underwent a laparotomy for a suspicion of ruptured ectopic pregnancy. The ectopic pregnancy was identified in the left remnant fallopian tube. Partial salpingectomy, removal of tubal stump, and resection of the uterine cornua, was performed. The postoperative recovery was uneventful. She has stayed for five days at the Hospital. All patients, even though they have already received a definitive contraception by tubal section and ligature or unilateral or by bilateral salpingectomy for any reason, must seek an ectopic pregnancy in case of pelvic pain, vaginal bleeding and/ or amenorrhea. Authors propose to carry a total salpingectomy after a chosen surgical treatment.